2012
DOI: 10.1002/ijc.27760
|View full text |Cite
|
Sign up to set email alerts
|

An association between clock genes and clock‐controlled cell cycle genes in murine colorectal tumors

Abstract: Disruption of circadian machinery appears to be associated with the acceleration of tumor development. To evaluate the function of the circadian clock during neoplastic transformation, the daily profiles of the core clock genes Per1, Per2, RevErba and Bmal1, the clock-controlled gene Dbp and the clock-controlled cell cycle genes Wee1, c-Myc and p21 were detected by real-time RT-PCR in chemically induced primary colorectal tumors, the surrounding normal tissue and in the liver. The circadian rhythmicity of Per1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0
5

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(49 citation statements)
references
References 50 publications
(122 reference statements)
0
44
0
5
Order By: Relevance
“…Recent studies have revealed that clock gene PER2 is reduced in various types of solid cancers, such as breast cancer, prostate cancer, and colorectal cancer (1,14,20,24), and PER2 can regulate downstream many cell cycle genes, such as CyclinA, CyclinB1, CyclinD1, and CyclinE; therefore, PER2 downregulation can lead to the process change of cell cycle, promote the growth of cancer cells, and inhibit apoptosis (27,29). Our previous research also proved that PER2 expression was reduced in human OSCC cells through the regulation of the downstream cell cycle gene, sequentially, which is closely related to the occurrence of cancers (30).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have revealed that clock gene PER2 is reduced in various types of solid cancers, such as breast cancer, prostate cancer, and colorectal cancer (1,14,20,24), and PER2 can regulate downstream many cell cycle genes, such as CyclinA, CyclinB1, CyclinD1, and CyclinE; therefore, PER2 downregulation can lead to the process change of cell cycle, promote the growth of cancer cells, and inhibit apoptosis (27,29). Our previous research also proved that PER2 expression was reduced in human OSCC cells through the regulation of the downstream cell cycle gene, sequentially, which is closely related to the occurrence of cancers (30).…”
Section: Discussionmentioning
confidence: 99%
“…PER2 is reduced in various types of cancer cells, including breast cancer, neck squamous cell carcinoma, prostate cancer, colorectal cancer, hepatocellular carcinoma, skin cancer, gastric cancer, and myeloid leukemia (1,10,14,(20)(21)(22)(23)(24)(25)(26). PER2 can regulate downstream plentiful cell cycle genes, such as CyclinA, CyclinB1, CyclinD1, CyclinE, p53, and C-myc (14,(27)(28)(29).…”
Section: Introductionmentioning
confidence: 99%
“…59,60 All of the foregoing show that functional circadian clock might operate as a tumor suppressor. 61 Further evidence that circadian clock is disrupted in cancer is shown in the study of Soták et al: 61 the expression profile of Dbp had robust circadian rhythmicity in the colonic mucosa of healthy mice and in the surrounding nonneoplastic tissue of tumor-bearing mice, but the amplitude of the tumors was reduced, and the amplitude was delayed. The rhythmic expression of core clock genes was markedly reduced in comparison with surrounding nonneoplastic tissue, and even more in comparison with colon mucosa of healthy animals.…”
Section: Circadian Rhythms and Cancermentioning
confidence: 94%
“…For example, in mice with lung adenocarcinoma, circadian gene expression was largely affected in the liver, with many genes losing rhythmicity, others becoming rhythmic, and some being shifted earlier or later [15]. In humans, alterations in clock gene expression and consequently clock-controlled gene expression was documented in the healthy gut tissues surrounding the tumor [18,19].…”
Section: Targeting the Clock In Tumors?mentioning
confidence: 99%
“…Notably, recent evidence indicates a significant reduction of circadian rhythmicity restricted to murine colon tumor tissue, whereas rhythms were unchanged in healthy colon tissue surrounding the tumor [19]. In fact, the intratumoral circadian disruption correlates with the patient's prognosis and survival [17,18].…”
Section: Targeting the Clock In Tumors?mentioning
confidence: 99%